The tales they tell about Year of Rat - Abd Razak, Dzulkifli (2008)
MANY will remember the Cinderella fairy tale where rats are magically transformed into horses and a pumpkin into a golden carriage for Cinderella to ride to the ball and meet her Prince Charming. Cinderella and the prince lived happily ever after. And how would your 2008 Year of the Rat be? Well, it all depends on who your favourite geomanceris. The one that I came across predicted something close enough to a Cinderellalike fairy tale. Short of saying that the Year of the Rat will be turned into the Year of the Horse, it was predicted that the coming Chinese New Year would be a galloping one nevertheless.